Phytochemical and Bioactivity Profile of Selected Medicinal Plants from Chitwan, Nepal - Gupta, Kanhaiya Lal; Sharma, Khaga Raj (BMC Journal of Scientific Research, 2025)
Plants have been primary source of medicines from time immemorial. The herbal resources have inspired the scientific community to regularly develop new drugs to combat the issues of multidrug-resistant (MDR) pathogens and the negative side effects of the present therapeutics. The study aimed to estimate the qualitative and quantitative phytochemical composition, antioxidant potential, and antibacterial activity of Artemisia vulgaris, Boerhavia diffusa, Ocimum sanctum, and Tinospora cordifolia collected from Bharatpur. The plant materials were extracted with methanol and water by cold percolation. Qualitative phytochemical analyses were conducted using standard color differentiation reactions, while quantitative analyses involved absorbance-based measurements. Antioxidant potential was determined by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method, while agar-well diffusion method was employed to estimate antibacterial activity against Staphylococcus aureus and Escherichia coli. Methanolic extracts exhibited higher phytochemical content and bioactivity. Among these, O. sanctum showed the highest total phenolic content (115.81 ± 3.58 mg GAE/g) and total flavonoid content (178.95 ± 21.95 mg QE/g), followed by B. diffusa, T. cordifolia, and A. vulgaris. O. sanctum also demonstrated the highest antioxidant potential with the lowest half-maximum inhibition concentration (IC50) value (100.43 ± 0.38 µg/mL), showing a strong correlation of phenolic and flavonoid contents with DPPH radical scavenging (p